The new music theater : seeing the voice, hearing the body - Salzman, Eric (Oxford University Press, 2008)
Introduction: What is Music Theater?. Part I: Music in Music Theater. 1. The Voice. 2. Where the Sound Comes From. 3. The Music. Entr'acte I: Is there such a thing as progress in music and music theater?. Part II: Theater in Music Theater. 4. Theater, Music, and Culture. 5. Text. Entr'acte II: The Language of Kathakali. 6. Visual Strategies. 7. Space. Entr'acte III: A Theater of Warm Bodies?. Part III: Putting it all together: La Mise en Scene. 8. The American Eccentrics. 9. Germany and Austria. 10. The Italians. Entr'acte IV: The In Between. 11. Music Theater in France. 12. Great Britain and.